Wild cities : discovering new ways of living in the modern urban jungle - Fitch, Chris, 1988- (William Collins, 2025)
Nature isn't a luxury, it's a necessity. But today the majority of the world's population lives in some form of urban environment. And by 2050, two-thirds of humanity will live in towns and cities. Studies have shown that a daily walk in the woods can improve our health and happiness, that those who can observe a natural scene through a hospital window will recover faster. The sound of birds, the smell of tree oils, the presence of free-flowing water - these are all vital to our wellbeing. So as the human footprint of brick, concrete and metal expands, how do we protect our connection to the natural world? In Wild Cities, Chris Fitch leads us around the world in search of answers, visiting pioneering cities and meeting the people working at the forefront of this issue. From the tiny urban forests in Tokyo and the star-rich skies of Flagstaff, to the meandering river of Munich and lions prowling through gardens in Nairobi, this is a globe-spanning look at how to bring nature into the places we live - and how to create the wild cities of the future.